1977
DOI: 10.1177/002221947701000710
|View full text |Cite
|
Sign up to set email alerts
|

The Slingerland Screening Tests

Abstract: In order to increase the utility of the Slingerland Screening Tests, percentile rank norms were calculated for 2272 elementary school students in grades K through 6. Tables of norms are presented for key percentile ranks. Separate tables of norms were calculated for males and females since significant mean sex differences were found. The split-half reliability coefficients obtained lend firm support to the notion that the tests are reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1981
1981
1984
1984

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…Similarly, McCandless (1972) says of the Boehm Test of Basic Concepts that "none of the criteria of formal test construction is satisfied." More recent studies by Burns and Burns (1977) Studies reporting measurement of predictive validity present a variable picture. Reasonable levels of predictive validity are reported for certain tests.…”
Section: Educational Screeningmentioning
confidence: 99%
“…Similarly, McCandless (1972) says of the Boehm Test of Basic Concepts that "none of the criteria of formal test construction is satisfied." More recent studies by Burns and Burns (1977) Studies reporting measurement of predictive validity present a variable picture. Reasonable levels of predictive validity are reported for certain tests.…”
Section: Educational Screeningmentioning
confidence: 99%
“…Based on a correlation coefficient of .57-.65, it was concluded that the Slingerland Screening Tests are useful predictive instruments, again supporting the validity of the instrument. In terms of reliability data, Burns and Burns (1977) tested all students in kindergarten through grade 6 in one school. Using a split-half reliability coefficient, they supported the Slingerland as a diagnostic instrument.…”
Section: The Slingerland Screening Testsmentioning
confidence: 99%
“…Burns and Burns (1977) published an article describing their development of local norms on the SST. Based on split-half reliability coefficients, they concluded that the tests were reliable.…”
mentioning
confidence: 99%